Transfert des apprentissages de VIH /SIDA chez les étudiants de la Faculté de Psychologie et des Sciences de l’Education de l’Université de Kisangani - LIKAMBELO, Fidèle LITIELO; ZOKO, Franck NGANGA (IJRDO- Journal of Educational Research, 2021)
This study related to the transfer of the trainings of VIH/AIDS in the students of the Faculty of Psychology and Sciences of the Education of the University of Kisangani. It was a question of evaluating the degree of transfer of the trainings has in VIH/AIDS at these students. With this intention, we had constituted an occasional sample of 50 subjects, the semi-structured interview supported by 8 situation-problems in sexual matter which one meets in the life allowed us to join together the data of this study.  With the exit of the analyses, it proved in a total way that, our inquired re-use their acquired knowledge of the course of the VIH/AIDS. The great majority controls the modes of contamination and prevention in VIH /AIDS.